How can we objectively categorise partnership type? A novel classification of population survey data to inform epidemiological research and clinical practice. (17th August 2016) - Mercer, C H; Jones, K G; Johnson, A M; Lewis, R; Mitchell, K R; Gravningen, K; Clifton, S; Tanton, C; Sonnenberg, P; Wellings, K; Cassell, J A; Estcourt, C S
Abstract : Background: Partnership type is a determinant of STI risk; yet, it is poorly and inconsistently recorded in clinical practice and research. We identify a novel, empirical-based categorisation of partnership type, and examine whether reporting STI diagnoses varies by the resulting typologies. Methods: Analyses of probability survey data collected from 15 162 people aged 16–74 who participated in Britain's third National Survey of Sexual Attitudes and Lifestyles were undertaken during 2010–2012. Computer-assisted self-interviews asked about participants' ≤3 most recent partners (N=14 322 partners/past year). Analysis of variance and regression tested for differences in partnership duration and perceived likelihood of sex again across 21 'partnership progression types' (PPTs) derived from relationship status at first and most recent sex. Multivariable regression examined the association between reporting STI diagnoses and partnership type(s) net of age and reported partner numbers (all past year). Results: The 21 PPTs were grouped into four summary types: 'cohabiting', 'now steady', 'casual' and 'ex-steady' according to the average duration and likelihood of sex again. 11 combinations of these summary types accounted for 94.5% of all men; 13 combinations accounted for 96.9% of all women. Reporting STI diagnoses varied by partnership-type combination, including after adjusting for age and partner numbers, for example, adjusted OR: 6.03 (95% CI 2.01 to 18.1) for men with two 'casual' and one 'now steady' partners versus men with one 'cohabiting' partner. Conclusions: This typology provides an objective method for measuring partnership type and demonstrates its importance in understanding STI risk, net of partner numbers. Epidemiological research and clinical practice should use these methods and results to maximise individual and public health benefit.